QUANTITATIVE ANALYSES ON THE EFFECTIVE HARDENING LAYER DEPTH OF GEAR - XIAO WeiZhong; LIU ZhongMing; YUAN YuPeng; YAN ShiDang (Jixie qiangdu)
Based on the relationship between shear stress and Hardness,using the linear regression method,the calculation formula of effective case depth of carburized gear was derived,and it was verified by example. The results show that the accuracy of the derived simple computational formula can meet the requirements for gear design. Using this formula,the effective case depth of gear was obtained,and the model for the distribution of effective case depth of gear was established.